Kepastian Hukum Bagi Tenaga Kerja Untuk Mendapatkan Upah Sesuai Keputusan Gubernur Jawa Barat Nomor : 561.7/Kep.776-Kesra/2022 - Febri Billiandro Sartono; Aditya Pangestu Halomoan Tampubolon; Donyuanalloh Azdy; Vehrial Vahzrianur; Ridho Witjaksono; Imam Wahyudi; Evi Yunita; Dicky Triantoro; Mustika Mega Wijaya (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
In Indonesia, there are many business entities to create jobs in order to reduce the unemployment rate. In general, business entities can be separated into 2, namely business entities in the form of legal entities and business entities that are not in the form of legal entities. Business entities in the form of legal entities, namely limited liability companies, state-owned companies, cooperatives, etc. Meanwhile, business entities that are not in the form of legal entities that are often encountered are firms, CVs, and limited partnerships. In running this business, a business entity requires a workforce that plays an important role in the running of the activities of a business. Labor is someone who does a job to produce goods or services to get wages so that they can fulfill their lives. Law Number 6 of 2023 concerning Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation Becomes an Act which aims to provide protection for every worker so that they are not treated arbitrarily, as well as guarantee certainty in life peace of mind for workers, to find out legal certainty for workers who work in business entities that are not legal entities. Wages that are needed by workers to meet their needs are very important. Therefore employers must pay wages in accordance with the minimum wage regulations set by governors in provincial areas and regents/mayors in urban areas. In addition, employers must guarantee that all workers who work in their company are peaceful, safe, and peaceful in carrying out their work. The purpose of this research is also as a science for readers to know that there is legal certainty that protects a worker in obtaining certainty in obtaining a job. matters and these matters cannot be contested.